Fluid flow in a porous medium with transverse permeability discontinuity - Pavlovskaya, Galina E.; Meersmann, Thomas; Jin, Chunyu; Rigby, Sean P. (American Physical Society, 2018)
Magnetic Resonance Imaging (MRI) velocimetry methods were used to study fully developed axially symmetric fluid flow in a model porous medium of cylindrical symmetry with a transverse permeability discontinuity. Spatial mapping of fluid ow resulted in radial velocity profiles. High spatial resolution of these profiles allowed the estimating of the slip in velocities at the boundary with a permeability discontinuity zone in a sample. The profiles were compared to theoretical velocity fields for a fully developed axially symmetric flow in a cylinder derived from the Joseph and Beavers and the Brinkman models. Velocity fields were also computed using pore-scale lattice Boltzmann Modelling (LBM) where the assumption about the boundary could be omitted. Both approaches gave a good agreement between theory and experiment though LBM velocity fields followed experiment more closely. This work shows great promise for MRI velocimetry methods in addressing the boundary behavior of fluids in opaque heterogeneous porous media.